Eksplorasi electronic word of mouth melalui Instagram, harga, micro influencer, dan perceived value pada minat Beli Nail Art - Novasa, Sheena Amelia; Kusuma, Pradana Jati (Nur Science Institute, 2025)
This study aims to examine the effects of Electronic Word of Mouth (E-WOM), price, micro influencers, and perceived value on purchase intention for Nail Art services at Sheeme Nails in Semarang, Indonesia. A quantitative survey design was employed, and data were collected through an online questionnaire using a five-point Likert scale. The study population consisted of Sheeme Nails customers, with a total of 170 respondents selected using purposive sampling. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The results reveal that E-WOM, micro influencers, and self-actualization perceived value have a positive and significant influence on purchase intention, while price and prestige perceived value show no significant effect. Furthermore, the interaction between self-actualization perceived value and E-WOM is significant, indicating that a stronger drive for self-actualization enhances the influence of E-WOM on purchase decisions. In contrast, interactions between self-actualization perceived value and both price and micro influencers are not significant, nor are any of the interactions involving prestige perceived value.